A RARE CASE OF CARDIOEMBOLIC STROKE IN PATIENT WITH CARDIAC MYXOMA: CASE REPORT - Wiracakra, I Gusti Lanang Krisna; Putri, Setyawati Asih (Jurnal Ilmu Kedokteran dan Kesehatan, 2023)
Abstract: A Rare Case of Cardioembolic Stroke in Patient with Cardiac Myxoma: Case Report. Cardiac myxoma is a condition where there is a tumor in the heart chambers, which is a rare cause of cardioembolic strokes in patients. The purpose of this case report is to convey a case that is rarely found in daily clinical practice as well as the stages of diagnosis and management of this case. A 42-year-old woman came with a sudden loss of consciousness, and after the patient regained consciousness, there was a neurological deficit. Based on the anamnesis, there was no history or risk factors for stroke in the patient. Through additional physical and supporting examinations, the patient was diagnosed with a cardioembolic stroke accompanied by cardiac myxoma. The patient received stroke therapy such as antiplatelet administration and physiotherapy to improve the condition of the patient's neurological deficits. After passing the treatment period, the patient's condition improved but still required further treatment.